The development of creativity of foreign language teachers as a factor in their subjective well-being - Kateryna S. Pavlenok; Olena I. Bondarchuk (Academy of Cognitive and Natural Sciences, 2024)
This study explored the level of creativity among 208 foreign language teachers in Ukraine. Results showed insufficient levels across value, cognitive and behavioural components of creativity. A training program was proposed to develop teacher creativity through 5 sessions targeting these components and psychological/organisational factors. Developing teacher creativity can support subjective well-being and success in creative teaching activities. The program contains informational, diagnostic, developmental and creative stages to enhance creativity and motivation. Further research could expand the criteria and methods for evaluating program effectiveness.